How to dissect : exploring with probe and scalpel - Berman, William (New York : Arco Pub., 1984)
A guide for dissecting animals, beginning with the earthworm and progressing to more complex anatomies such as grasshopper, starfish, perch, and ultimately a fetal pig. Includes a chapter on dissecting flowers.
Includes index.
Keywords: Dissection -- Juvenile literature; Dissection; Anatomy